Connectivity and knowledge management in virtual organizations : networking and developing interactive communications - Camison, Cesar, 1958- (Hershey, PA : Information Science Reference, 2009)
'This book analyzes different types of virtual communities, proposing Knowledge Management as a solid theoretical ground for approaching their management'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 356-408) and index.
Keywords: Virtual reality in management; Knowledge management; Virtual corporations -- Management; Information networks